2019
DOI: 10.3892/ol.2019.11151
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‑106a enhances oxaliplatin sensitivity of colorectal cancer through regulation of FOXQ1

Abstract: Chemotherapy resistance poses a major challenge for the clinical treatment of colorectal cancer, therefore, the aim of the present study was to examine its underlying mechanisms. Reverse transcription-quantitative polymerase chain reaction and western blot analysis were used to determine the microRNA (miRNA)/mRNA and protein expression levels, respectively. A dual luciferase assay was conducted for verification of the interaction between miR-106a and 3′untranslated region (UTR) of Forkhead box Q1 (FOXQ1). Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“… 59 It was shown that miR-106a is involved in the regulation of CRC oxaliplatin sensitivity. 60 miR-106a transfection mildly suppressed the growth of CRC cells and rendered them more sensitive to oxaliplatin. Furthermore, miR-106a overexpression decreased the FOXQ1 level in CRC cells at both mRNA and protein levels.…”
Section: Mirnas and Response To Chemotherapy In Gi Cancermentioning
confidence: 97%
See 2 more Smart Citations
“… 59 It was shown that miR-106a is involved in the regulation of CRC oxaliplatin sensitivity. 60 miR-106a transfection mildly suppressed the growth of CRC cells and rendered them more sensitive to oxaliplatin. Furthermore, miR-106a overexpression decreased the FOXQ1 level in CRC cells at both mRNA and protein levels.…”
Section: Mirnas and Response To Chemotherapy In Gi Cancermentioning
confidence: 97%
“…They concluded that miR-106a increased CRC sensitivity to oxaliplatin through direct suppression of FOXQ1 expression. 60 miR-744 was upregulated in head and neck tumors compared to normal tissues. 61 High plasma levels of miR-744 correlated with chemoresistance and poor prognosis in patients with PC undergoing gemcitabine-based chemotherapy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, miR-106a can suppress the transcription of VEGFA and MMP-2, which are target genes for FOXQ1. 54 MiR-135b functions as a tumor promoter in colorectal cancer. The miR-135b expression is remarkably elevated in colorectal cancer cell lines.…”
Section: Micrornas Regulating Cancer Cell Response To Oxaliplatin In ...mentioning
confidence: 99%
“…The miRNA-106a function in chemotherapy has not been completely understood. Although studies demonstrate that miRNA-106a has low expression in chemo-resistant-tumour cells and elevating its expression is correlated with chemosensitivity (Refs 174, 175), a recent study demonstrated miRNA-106a function in providing drug resistance via JAK2/STAT3 axis induction (Ref. 176).…”
Section: Micrornas and Sox2mentioning
confidence: 99%